2016
DOI: 10.1126/sciadv.1600664
|View full text |Cite
|
Sign up to set email alerts
|

Self-optimized superconductivity attainable by interlayer phase separation at cuprate interfaces

Abstract: Resolving how and why maximized superconducting amplitude can be self-organized at interfaces opens perspectives for design.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 52 publications
(86 reference statements)
2
11
0
Order By: Relevance
“…The exact answer is not available even for the simple Hubbard model, and the quantitative range of the superconducting dome as well as the charge inhomogeneous region depend on details of the accuracy in numerical methods ( 4 9 , 21 23 ). However, the tight connection between the superconductivity and the charge inhomogeneities is a widely observed tendency ( 2 9 , 25 ) in accordance with the tendency in the experimental observations ( 1 ). The strong-coupling superconductivity can be achieved only when the effective attractive interaction becomes strong, whereas too strong static attraction results in the abovementioned aggregation of electrons with charge inhomogeneity, which constitutes a “double-edged sword.”…”
Section: Resultssupporting
confidence: 82%
“…The exact answer is not available even for the simple Hubbard model, and the quantitative range of the superconducting dome as well as the charge inhomogeneous region depend on details of the accuracy in numerical methods ( 4 9 , 21 23 ). However, the tight connection between the superconductivity and the charge inhomogeneities is a widely observed tendency ( 2 9 , 25 ) in accordance with the tendency in the experimental observations ( 1 ). The strong-coupling superconductivity can be achieved only when the effective attractive interaction becomes strong, whereas too strong static attraction results in the abovementioned aggregation of electrons with charge inhomogeneity, which constitutes a “double-edged sword.”…”
Section: Resultssupporting
confidence: 82%
“…Understanding their common route and distinctions revealed here will help designing ways of suppressing the stripe and stabilizing the SC state simultaneously. Some attempts were already made 16,65 , and extensive studies along this line are intriguing challenging issues in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Also the critical current density J c depends on the d/l s ratio. From ESCM it follows that J c ≈ J cb (1 -2l s /d) 3 , where J cb is the critical current density of the sample with d >> l s [11]. This relation allows us to estimate the d/l s ratio from the observed asymmetry of magnetization loops.…”
Section: Resultsmentioning
confidence: 97%
“…Recently [2,3], it was shown that an interface superconductivity arises on the boundary of LCO and La 1.56 Sr 0.44 CuO 4 films. Study of such films is limited by the complexity of their synthesis (a layer-by-layer molecular beam epitaxy).…”
Section: Introductionmentioning
confidence: 99%